1980
DOI: 10.1055/s-0038-1650084
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Platelet Aggregation by Bile Salts

Abstract: SummaryIn a series of in vitro experiments, the influence of bile salts on platelet aggregation by ADP or by collagen and on serotonin-14C release by collagen, was studied.Sodium salts of the following bile acids showed a clear inhibitory effect: glycochenodeoxycholic acid, taurochenodeoxycholic acid, glycocholic acid, taurocholic acid and cholic acid. Lowering the pH of the platelet-rich plasma resulted in decreased platelet aggregation by ADP and by collagen. Bile salts further enhanced the inhibitory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Bile salts can also exert a negative effect. In vitro aggregation studies show an inhibitory effect of bile salts on platelet aggregation and serotonin release induced by ADP or collagen 88 . Only chenodeoxycholic acid is an aggregation‐inducing bile salt 88 .…”
Section: Platelet Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bile salts can also exert a negative effect. In vitro aggregation studies show an inhibitory effect of bile salts on platelet aggregation and serotonin release induced by ADP or collagen 88 . Only chenodeoxycholic acid is an aggregation‐inducing bile salt 88 .…”
Section: Platelet Functionmentioning
confidence: 99%
“…In vitro aggregation studies show an inhibitory effect of bile salts on platelet aggregation and serotonin release induced by ADP or collagen 88 . Only chenodeoxycholic acid is an aggregation‐inducing bile salt 88 . In vivo studies in rat models associated with elevated bile acids (bile duct ligation and cholic acid feeding) show a clear inhibitory effect on ADP‐epinephrine induced aggregation 89 …”
Section: Platelet Functionmentioning
confidence: 99%
“…In diets containing cholesterol and cholic acid (CA), increased thrombin and adenosine diphosphate (ADP)-induced platelet aggregation and an acceleration of the platelet-rich plasma clotting time were found (McGregor et al, 1980 ). Other authors, however, observed that sodium salts of some bile acids, such as cholic acid, showed a clear inhibitory effect on platelet aggregation by ADP, while the sodium salt of chenodeoxycholic acid (CDA) was an inducer of platelet aggregation (Baele et al, 1980 ). In other experiments, deoxycholic acid inhibited platelet aggregation and ADP secretion in platelets activated with either collagen or thrombin (Tan et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of platelet counts within normal limits depends on the ability of bone marrow to increase production, which is reflected in the proportion of young elements in the circulation. Although thrombocytopoiesis is under the direct effect of thrombopoietin, a growth factor synthesized mainly by the liver and the kidney, and whose serum levels decrease in advanced cirrhosis and portal hypertension, its titers do not correlate directly with medullary platelets synthesis (8). This apparent discordance results from the fact that the removal of thrombopoietin from the circulation is made through its internalization in megakaryocytes and platelets, including those which are pooled in the spleen (9).…”
Section: Discussionmentioning
confidence: 99%